A new chapter in the law of sexual harassment in Malaysia: The emergence of the torts of harassment and sexual harassment. (December 2019) - Majid, Abdul; Yogamalar, Sri; Siah, Audrey Kim Lan; Terpstra-Tong, Jane L Y; Borrowman, Luc
In a landmark case in 2016, Malaysia's apex court, the Federal Court, explicitly recognised for the first time, the common law tort of sexual harassment. Actually, the Federal Court did more than that; its recognition of the common law tort of sexual harassment is built on its recognising the common law tort of harassment. The recognition of the tort of harassment has escaped notice because attention has been concentrated on the tort of sexual harassment. This article analyses the Federal Court's exposition of the tort of sexual harassment to reveal that the exegesis itself acknowledges the existence of the tort of harassment per se. The tort of harassment that the Federal Court sent out into the world is largely a creature of its English common law ancestry.